Heparin-induced Thrombocytopenia: Towards Consensus - Warkentin, Theodore E.; Chong, Beng H.; Greinacher, Andreas (Thrombosis and Haemostasis, 1998)
Heparin-induced thrombocytopenia (HIT) is a drug-induced, immunoglobulin-mediated thrombocytopenic disorder that is important for at least three reasons. First, it is a relatively common drug-induced immunohematologic adverse reaction. Second, it is frequently complicated by life- and limb-threatening thrombotic complications. And third, there remains uncertainty about the optimal treatment approach for these patients. Recently, there has emerged increasing consensus on such important issues as the frequency, pathogenesis, and diagnostic testing, which we will summarize here. Further, a greater appreciation of the activation of the coagulation pathways in this syndrome indicate a rationale to treatment approaches that emphasize thrombin inhibition (eg. danaparoid sodium; hirudin and its analogues).